From one school to many: Reflections on the impact and nature of school federations and chains in England. (January 2015) - Chapman, Christopher
School-to-school collaboration has been central to many improvement efforts over recent decades. In an attempt to promote both improvement and equity current developments in England have included changing formal governance arrangements to promote collaboration for improvement through 'federations' and 'chains' of schools. However, federations and school chains remain a relatively under-explored area and there is a noticeable absence of research exploring the impact of such arrangements on student outcomes. This paper draws on a programme of research including the national evaluation of federations, the first quantitative study of the impact of federations on student outcomes and a longitudinal qualitative study of the development of federations to consider two key questions: What is a federation? And do federations make a difference? In order to achieve this, the paper provides an overview of the key characteristics of federations and considers their contribution to improvement efforts. In conclusion the paper reflects on a number of issues and implications associated with developing a federated school system.